Implemenasi Sistem Sharia Crowdfunding terhadap Efektivitas Penghimpunan Dana Zakat, Infaq dan Shadaqah (Studi pada Wahdah Inspirasi Zakat Kota Makassar) - Nurhalima, Nurhalima; Muslihati, Muslihati; Putra, Trisno Wardy (ISLAMIKA, 2024)
This investigation intends to sort out how the sharia crowdfunding structure is completed in social occasion zakat, infaq and shadaqah resources at Wahdah Inspirasi Zakat, Makassar City. This sort of assessment uses emotional procedures with a humanistic juridical philosophy, the data sources used are fundamental and discretionary data, then, the data collection strategies used are discernment, gatherings and documentation. The data examination strategies used are data combination, data decline, data show, closures and affirmation. The eventual outcomes of this investigation show that the utilization of the sharia crowdfunding system in social affair zakat, infaq and shadaqah resources at Wahdah Inspirasi Zakat, Makassar City has experienced an addition of up to 80% during the use of crowdfunding because there are 2 models of crowdfunding stages used in get-together zakat, infaq and shadaqah reserves. can assist with expanding the assortment of zis reserves, to be specific boxinfak.id and wiz gifts. boxinfak.id and wiz gifts are utilized in gathering zakat, infaq and shadaqah reserves or muzakki in paying zakat, infaq and sadaqah, utilizing the crowdfunding framework truly helps the amil or muzakki in gathering or paying zakat, infaq and sadaqah.